Assessing the coverage of full antenatal care among adolescent mothers from scheduled tribe and scheduled caste communities in India - Aditya Singh; Vineet Kumar; Harpreet Singh; Sourav Chowdhury; Sanjana Sharma (BMC, 2023)
Abstract Background The persistently high rates of maternal mortality and morbidity among historically marginalised social groups, such as adolescent Scheduled Castes (SCs) and Scheduled Tribes (STs) in India, can be attributed, in part, to the low utilisation of full antenatal healthcare services. Despite efforts by the Indian government, full antenatal care (ANC) usage remains low among this population. To address this issue, it is crucial to determine the factors that influence the utilisation of ANC services among adolescent SC/ST mothers. However, to date, no national-level comprehensive study in India has specifically examined this issue for this population. Our study aims to address this research gap and contribute to the understanding of how to improve the utilisation of ANC services among adolescent SC/ST mothers in India. Data and methods Data from the fourth round of the National Family Health Survey 2015-16 (NFHS-4) was used. The outcome variable was full antenatal care (ANC). A pregnant mother was considered to have 'full ANC' only when she had at least four ANC visits, at least two tetanus toxoid (TT) injections, and consumed 100 or more iron-folic acid (IFA) tablets/syrup during her pregnancy. Bivariate analysis was used to examine the disparity in the coverage of full ANC. In addition, binary logistic regression was used to understand the net effect of predictor variables on the coverage of full ANC. Results The utilisation of full antenatal care (ANC) among adolescent SC/ST mothers was inadequate, with only 18% receiving full ANC. Although 83% of Indian adolescent SC/ST mothers received two or more TT injections, the utilisation of the other two vital components of full ANC was low, with only 46% making four or more ANC visits and 28% consuming the recommended number of IFA tablets or equivalent amount of IFA syrup. There were statistically significant differences in the utilisation of full ANC based on the background characteristics of the participants. The statistical analysis showed that there was a significant association between the receipt of full ANC and factors such as religion (OR = 0.143, CI = 0.044-0.459), household wealth (OR = 5.505, CI = 1.804-16.800), interaction with frontline health workers (OR = 1.821, CI = 1.241-2.670), and region of residence in the Southern region (OR = 3.575, CI = 1.917-6.664). Conclusion In conclusion, the study highlights the low utilisation of full antenatal care services among Indian adolescent SC/ST mothers, with only a minority receiving the recommended number of ANC visits and consuming the required amount of IFA tablets/syrup. Addressing social determinants of health and recognising the role of frontline workers can be crucial in improving full ANC coverage among this vulnerable population. Furthermore, targeted interventions tailored to the unique needs of different subgroups of adolescent SC/ST mothers are necessary to achieve optimal maternal and child health outcomes.